Architect's essentials of contract negotiation : - Abramowitz, Ava J. (John Wiley & Sons, 2002)
For architects, negotiation is explicit in every aspect of practice, just as it is implicit in every aspect of design. And now you can develop or refine the negotiation skills you need with the help of this concise, easy-to-follow guide. Written by an acknowledged expert in the field, this volume in the Professional Practice Series offers accessible, practical coverage of contract negotiation essentials related to growth, expansion, new management, internal transitions, mergers, acquisitions, liquidations, retirement, and more. Also, like all the books in this series, the information you'll find here is expressly tailored to the needs of the design professional.